PROPOSTA DE MAPEAMENTO E MELHORIA DE PROCESSO DE IMPORTAÇÃO: UM ESTUDO DE CASO - Bastos, Francisco Carlos Pereira (2013)
This study intends to contribute to the improvement of the importation process the IRD / CNEN, basing future initiatives in BPM. Through a literature review, were discussed trends in the management of organizations - emphasized that the change in paradigms tends to process management. Characterized the type of structure of the Institute and, unfolding it to get to the import process, we performed the mapping process that drowned the block diagram and the map of the current process. These two instruments demonstrated the flow operational and the opportunities found to perform the improvements. Was emphasized the time spent between the beginning and the end of the importation. A focus group was formed to validate the problems found and opining on the solutions proposals. From these opinions, redrew new diagram of blocks and new map of the process. As a result of the intended improvements, a reduction of the process total time from its inception until the delivery of importation to the internal customer.